Sikap Netral Alumni STIP-AN Sebagai Aparatur Sipil Negara Dalam Mengimplementasikan Kebijakan Pemerintahan DI Era Demokratisasi Kehidupan Politik - Hamim, Sofyan Safari (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2015)
Neutral attitude of alumni of STIP-AN as civil servant and as The Indonesian Civil Service Corps (Korpri) member on implementing the goverment policies in democratization era of political life will be run well, if it started from the system of servant recruitment, and the development with servant safety webs system consist of basic measurement, purepose, source of neutrality policies, communication between organizaions, characteristic of implementing agent, and inclination of implementer, and also supporting tolls. Neutrality will be related to professionalism and servant's welfare which its quality depends on bureaucracy ethics and social ethics that have equality value and individual rights guaranty. The implementation of neutral attitude of civil servant of The Indonesian Civil Service Corps (Kopri) is as service action, empowerment and the development which is did by civil servant of The Indonesia Civil Service Corps (Korpri) member for reaching purpose consist of effort to discuss, to create the common good about all the things of state administation and regional on finding and maintaining authority, formulating and implementing public policies, also finding and maintaining the important resources. For the run of goverments wheel in effective, efficient and equity for the implementation of national and regional development, hope that this can be understandable, respected in propotional, in consistency by alumni of STIPAN as civil servant of The Indonesia Civil Service Corps (Korpri) and all of nation components